1983
DOI: 10.1016/0035-9203(83)90064-0
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of auto-antibodies in malaria and the role of polyclonal activation

Abstract: Sera of 173 individuals living in a malaria endemic region in Upper Volta (Donsé village) were screened for the presence of 14 auto-antibodies by the indirect immunofluorescent and/or passive haemagglutination techniques. At least one auto-antibody (AAb) was detected in sera of 72% (124 out of 173) subjects. No differences in the AAb frequency was observed in the sex or age groups. Conversely, a significant relationship between a high frequency of auto-antibodies, high malaria antibody titres and high IgM leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…�his finding agrees with previous works showing that anti-thyroid peroxidise antibodies and anti-thyroglobulin antibodies are absent during human or murine malaria infections (Daniel-Ribeiro et al 1983, 1984a. �o our knowledge, our study is the first to indicate that anti-vimentin, anti-glomerular basement membrane, anti-gastric parietal cell, anti-intercellular substance, muscle-specific tyrosine kinase and anti-liver kidney microsomal type 1 auto-Ab can react against plasmodial antigens.…”
Section: Discussionsupporting
confidence: 83%
“…�his finding agrees with previous works showing that anti-thyroid peroxidise antibodies and anti-thyroglobulin antibodies are absent during human or murine malaria infections (Daniel-Ribeiro et al 1983, 1984a. �o our knowledge, our study is the first to indicate that anti-vimentin, anti-glomerular basement membrane, anti-gastric parietal cell, anti-intercellular substance, muscle-specific tyrosine kinase and anti-liver kidney microsomal type 1 auto-Ab can react against plasmodial antigens.…”
Section: Discussionsupporting
confidence: 83%
“…In Jacareacanga, there was a positive relationship between malaria (any past reported cases) and likelihood of elevated ANoA. We examined these potential biological interactions among mercury, malaria, and autoimmune biomarkers further, because of studies demonstrating that repeated malaria infections are associated with increased levels of autoantibodies, including ANA, presumably due to cytotoxic damage and exposure of intracellular epitopes [44,45]. Other studies have shown that autoantibodies are produced in mice infected with malaria, which react with several nuclear antigens, namely RNA, soluble nuclear material and DNA [46].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, numerous biological signs of autoimmunisation are apparent in the course of acute disease or among individuals chronically exposed to infection. These signs relate to AAg such as double and single stranded DNA (Quakyi et al 1979, Daniel-Ribeiro et al 1984b, Zouali et al 1986), erythrocyte (Facer et al 1979, Facer 1980, Lefrançois et al 1981, 1982, lymphocyte (De Souza & Playfair 1983), phospholipid (Bate et al 1992a, b, Facer & Agiostratidou 1994, Bordmann et al 1998, ribonucleoprotein (Greenwood et al 1970a, Daniel-Ribeiro et al 1983, 1991, Zouali et al 1986), RNA (Kreier & Dilley 1969), and smooth muscle (Quackyi et al 1979, Daniel-Ribeiro et al 1991 Ag and not to relate to organ-specific partially sequestered AAg such as thyroglobulin (DanielRibeiro et al 1984a). This suggests that the formed AAb would result from specific activation of autoreactive B-lymphocytes and not from the activation of these cells within the framework of a generalised polyclonal B-cell activation (PBA) (Daniel-Ribeiro et al 1984a, Daniel-Ribeiro 1988.…”
Section: Autoimmunity In the Course Of Malaria Infectionmentioning
confidence: 99%
“…In this way, anti-nuclear Ab (ANA) are often observed in immune animals and among individuals chronically exposed to infection (Poels et al 1980, Daniel-Ribeiro et al 1983, while smooth muscle Ab (SMA) are detected in the course of the acute infection (Quackyi et al 1979, Poels et al 1980, Ben-Slama 1982, Daniel-Ribeiro et al 1991. Since it has been clearly shown in man, at least as far as ANA and anti-SMA are concerned, that the production of AAb during malaria does not depend on racial factors (Voller et al 1972, Daniel-Ribeiro et al 1991, these observations suggest the existence of a correlation between autoreactivity and immune-protection or degree of exposure to malaria.…”
Section: Autoimmunity In the Course Of Malaria Infectionmentioning
confidence: 99%